Patient-informed outpatient intervention to improve pregnancy outcomes through connections to social services: protocol for the BETTER randomised controlled trial - William A Grobman; Laura J Rush; Ann Scheck McAlearney; Anna Bartholomew; Timothy R Huerta; Sarah R MacEwan; Nicole R Thomas; Lindsey N Sova; Leah Roth; Kaprea F Johnson (BMJ Open)
Introduction A substantial portion of the 3.6 million births per year in the USA (approximately 25%–30%) occur in the context of adverse pregnancy outcomes (APOs), including preterm birth (PTB), hypertensive disorders of pregnancy (HDP) and small-for-gestational-age (SGA) birth. Black individuals have a 2–3-fold higher risk of APOs and a similarly increased risk of maternal morbidity and mortality compared with White individuals. Adverse social determinants of health (SDoH) are at the root of this disparity and contribute to it through multiple mechanisms. Maternal anaemia is an upstream factor associated with severe maternal morbidity, maternal mortality and other APOs and is also associated with adverse SDoH. Effectively and efficiently addressing social needs arising from adverse SDoH in the obstetric setting can be difficult due to varying patient preferences, resource accessibility and clinic workflows. The Better Birth Outcomes Through Technology, Education and Reporting (BETTER) intervention attempts to account for these barriers by encouraging patients to address social needs through motivational interviewing and by sending recurring text messages that provide links to multiple kinds of social service resources.Methods and analysis We will use a two-arm randomised controlled trial to evaluate the effects of providing patients with a motivational interviewing session and text messages with links to multiple resources to address their social needs compared with patients receiving usual care. We will recruit 550 pregnant individuals less than 21 weeks of gestation from two university prenatal clinics that primarily serve Medicaid-covered individuals in an urban city in the Midwestern USA. We will assess whether the intervention reduces the primary outcome of maternal anaemia measured as haemoglobin <11.0 g/dL at delivery as well as important secondary outcomes, including PTB, HDP and SGA. We will also explore patient-reported outcomes, including how the intervention impacts patient global health, activation, self-efficacy, perceived stress, anxiety, depression and communication with their providers. A subgroup of participants from the intervention group will be interviewed up to 12 weeks postpartum about their experiences.Ethics and dissemination The Ohio State University (OSU) Institutional Review Board (IRB) approved this study (IRB: 2023H0065; date: 21 February 2024). All protocol amendments will be communicated for approval to the OSU IRB. We plan to share results in peer-reviewed journal articles and academic conferences as well as with the larger American Heart Association (AHA) Pregnancy, Postpartum and Postnatal Health: Enhancing Quality and Access to Achieve Equitable Maternal and Infant Health (P3 EQUATE) Network on maternal health, including clinicians, community members and social service providers. Following the trial, we will make deidentified data publicly available in compliance with AHA policy and federal regulations.Trial registration number NCT06261398.